Características morfométricas, merísticas, físicas y químicas del barbudo silvestre (Rhamdia cinerascens) en la zona de Babahoyo - 2017. - Matamoros Arechua, Ana Gabriela (2017)
The present investigation was carried out in the Babahoyo River and in the experimental farm "La María" belonging to Quevedo State Technical University (UTEQ), located at km 7 of the Quevedo - El Empalme road. Morphometric and meristic characteristics were evaluated and physical-chemical analyzes were performed. 255 samples were taken in different sites of the Babahoyo River. The variables evaluated were weight in grams, head width (LC1), trunk width (LC2), tail width (LC3), perimeter at the first radius of the dorsal fin (PC1), perimeter at the level Last radius of the dorsal fin (PC2), perimeter at the first radius of the anal fin (PC3). It used 255 bearded, with an average weight of 75-175 gr. In morphometry, the correlation values did not exceed 0.8, which shows that there is a stable relationship between, the variables studied in mention, in meristic, the frequencies of the radii; Dorsal, ventral, pectoral, anal, was mainly between 6 and 7, being an excellent variety, in the descriptive statistics applied in these variables.